Motivation of Generation Z at Work - Bambang Septiawan; Endah Masrunik (Trunojoyo University of Madura, 2020)
This study aims to analyze the work motivation of Sultan Coffee employees in line with the main theories, process theories, and contemporary theories. The subjects of this research were 4 employees of Sultan Coffee, who were classified as Gen Z. This research is qualitative and focuses on descriptive description because it aims to test the theory mentioned earlier. The results of the study show that the work motivation of the Z generation of sultan coffee employees is proven to be in accordance with the three theories. Specifically to fulfill their interests, the work environment is full of peers, and to carry out the mandate of their teacher.